Wearable sensor technology in sports monitoring - Espinosa, H.; Mears, A.; Stamm, A.; Ohgi, Y.; Coniglio, C. (Sports Engineering, 2025)
Wearable technology has become a pivotal tool in sports, revolutionizing how athletes train, compete, and recover. These devices, ranging from smartwatches and fitness trackers to advanced sensors embedded in clothing, provide real-time data on key performance metrics such as heart rate, speed, distance, and muscle activity. By offering actionable insights, wearables enable athletes and coaches to fine-tune training programs, monitor progress, and identify areas for improvement. In elite sports, where marginal gains can mean the difference between victory and defeat, wearables provide a competitive edge by facilitating personalized and data-driven strategies.